Dosimetric quantities and cell survival for spatially fractionated radiation therapy - Ahmed, Mabroor; Bicher, Sandra; Stewart, Robert D.; Bartzsch, Stefan; Schmid, Thomas E.; Combs, Stephanie E.; Meyer, Juergen (Frontiers in Physics, 2023)
Purpose: Spatially Fractionated Radiation Therapy (SFRT) is characterized by large differences in peak and valley doses. Preclinical and clinical studies suggest that differences in biological mechanisms lead to differential normal tissue and tumor response compared to uniform irradiation. We hypothesize that to evaluate clinical effectiveness and understand fundamental biological mechanisms, radiobiological rather than physical dose quantities should be utilized for comparisons. The aim of this work is to determine whether Equivalent Uniform Dose (EUD) is a superior predictor of cell survival than absorbed dose. Methods: Absorbed dose parameters were compared to EUD to assess their predictive value for the relative effectiveness of uniform and SFRT with X-rays. A Bayesian bootstrap technique was utilized to model uncertainties in the biological fit parameters for a human fibroblast (MRC5) and two human tumor cell lines (LN18 and A549). Dose uncertainties were evaluated through measurements and error modeling of SFRT profiles. A dimensionless Relative Effectiveness Factor (REF) is proposed to quantify differences between uniform and SFRT irradiation. Results: For all cell lines, survival after SFRT matched uniform irradiation within the estimated uncertainties at equal values of the EUD. Average and peak dose showed poor correlation with in vitro cell survival. The proposed REF factor is dose dependent and suggests enhanced cell killing for both tumor cell lines (1.14±0.08 for LN18, 1.32±0.13 for A549 at 8 Gy EUD) for SFRT. Normal human fibroblasts showed reduced cell killing relative to uniform irradiation (0.58±0.06 for MRC5). Synthetically generated SFRT dose profiles revealed that EUD uncertainties are dominated by valley dose uncertainties, especially at high doses. Discussion: EUD is considerably more predictive of cell survival than average or valley dose. Valley dose is close to equal to the EUD for values >10 Gy and has the advantage of being independent of uncertainties in biological parameters. The REF is a novel and useful metric to compare quantitative differences in SFRT and uniform irradiation. Conclusion: EUD is recommended for comparisons of SFRT and uniform irradiation. The results suggest an increase in survival of normal-human fibroblast cells and reduced survival for both tumor cell lines after SFRT relative to uniform irradiation.